?SEASONAL VARIATION IN THE COMPOSITION OF ESSENTIAL OIL OF EUCALYPTUS CAMALDULENSIS FROM·PAKISTAN: Short Communication (Biological Sciences - PJSIR, 1999)
The oil was examined on a Pye-Unicam 104 gas chramatographwith FID detector and WCOT-SE-30 column. Variouscomponents were identified by their retension time andco-injection of standard samples (Singh and Sinha 1981).Percentage composition of individual components wascalculated on the basis of peak area using SP-41 00 (Spectra-Physics) computing integrator.